Immune Checkpoint Inhibitor-Associated Colitis: From Mechanism to Management - Tang, Liansha; Wang, Jialing; Lin, Nan; Zhou, Yuwen; He, Wenbo; Liu, Jiyan; Ma, Xuelei (Frontiers in Immunology, 2021)
Immune checkpoint inhibitors (ICIs), as one of the innovative types of immunotherapies, including programmed cell death-1 (PD-1), programmed cell death-ligand 1 (PD-L1), and cytotoxic T lymphocyte antigen 4 (CTLA-4) inhibitors, have obtained unprecedented benefit in multiple malignancies. However, the immune response activation in the body organs could arise immune-related adverse events (irAEs). Checkpoint inhibitor colitis (CIC) is the most widely reported irAEs. However, some obscure problems, such as the mechanism concerning gut microbiota, the confusing differential diagnosis with inflammatory bowel disease (IBD), the optimal steroid schedule, the reintroduction of ICIs, and the controversial prognosis features, influence the deep understanding and precise diagnosis and management of CIC. Herein, we based on these problems and comprehensively summarized the relevant studies of CIC in patients with NSCLC, further discussing the future research direction of this specific pattern of irAEs.